Special issue on wood tech : First International Conference on Environmentally Compatible Forest Products - Jorge, Fernando Caldeira (Management of environmental quality, 2004)
The paper identifies and assesses the potential environmental burdens associated with the life cycle of printing and writing paper produced in Portugal from Eucalyptus globulus and consumed in Germany. Life cycle assessment methodology is applied in accordance with International Organization for Standardization standards. The life cycle of printing and writing paper covers the following stages: forest, pulp production, paper production, final disposal, energy production, chemical production and transports. The results suggest that pulp production processes have an important contribution to wat.